THE EFFECTS OF USING PODCASTS IN THE TEACHING OF LISTENING ON STUDENTS’ LISTENING COMPREHENSION ACHIEVEMENT - Zahrok, Umi Rohiyatul (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2024)
The use of podcast in the world of education has been going on for a while, but some experts still have different opinions about the benefits of it for the education itself. The aim of this research was to investigate whether or not students who were taught listening by using podcasts get higher score on their listening comprehension test compare to other students who were taught listening by using non-podcasts materials. This study was a quasi-experimental post-test only design which employed eleventh graders majoring mathematics and natural sciences 1 as the control group and eleventh graders of mathematics and natural sciences 2 as the experimental group. The research itself lasted for 5 meetings, 4 meetings were used as teaching and learning process and 1 meeting for post-test. The data of this study were collected by using multiple choice listening comprehension test. The data that were obtained were then analyzed by using independent sample t-test and calculated through the use of SPSS 16 with 5% (0.05) significant level. Based on the result of the data analysis, there is no significant effect on using podcasts in the teaching of listening on students’ listening comprehension achievement. In summary, it can be concluded that students who were taught listening by using podcasts do not get better score on their listening comprehension test than those who were taught listening by using non-podcasts materials.